A função do equilíbrio na relação intérprete-compositor - Herivelto Brandino (2012)
This paper aims to describe and discuss through the presentation of literature the composer-performer relationship in many ways, with the primary focus on the equality of interests of the musicians involved. Some situations were noted in which performers prioritize the characteristics of the instruments, and composers the characteristics of musical works. This is caused mainly by traditional education of musicians, which prescribes specific roles for each and creates different environments between composition and interpretation. The result is the lack of communication and consistency regarding all the process that involves the creation, execution and reception of the work. The equality thus works as a tool to get the highest potential of each musician and raise discussions with maximum reflection, without imposing ideas. Serving as another way to approach the object of study, the last part is the description of two moments in which the author experienced as a performer the performer-composer relationship. The equality could be applied and better understood in this process.